2023
DOI: 10.1002/agj2.21264
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of long‐term fertilization on crop yield and microbial communities under rice–rapeseed rotation

Abstract: Soil microbes play an integral role in agricultural production and soil fertility, while limited information is available about the effects of long‐term fertilization on rice (Oryza sativa L.)–rapeseed (Brassica napus L.) rotation yield, soil properties, and microbial communities in central China. Here, we report the response of plant–soil system to different mineral fertilizer inputs, including the balanced fertilization with N, P, and K (NPK) fertilizers and unbalanced fertilizers without one of the major nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The research results of Li [39] and Wasaki [40] are consistent with those of this study. However, Li [20] reported that the long-term application of NK increased the soil microbial composition and diversity, while the PK and NP treatments had the opposite effect. This contradiction may be related to differences in soil fertility levels and the duration of field trials.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The research results of Li [39] and Wasaki [40] are consistent with those of this study. However, Li [20] reported that the long-term application of NK increased the soil microbial composition and diversity, while the PK and NP treatments had the opposite effect. This contradiction may be related to differences in soil fertility levels and the duration of field trials.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have shown that chemical fertilizer input mainly affects the growth and activity of microorganisms by altering the amount of nutrients in the soil [18,19]. The reasonable application of chemical fertilizers can effectively supplement the absorption of large amounts of nutrients from the soil due to crop growth and development and alleviate the limitation of soil nutrient loss on microbial growth [20,21]. The excessive application of chemical fertilizers can lead to soil nutrient imbalances.…”
Section: Introductionmentioning
confidence: 99%